Characteristics of electomagnetic and magneto-static surface waves in metal-dielectric-ferrite-left handed waveguide layered structure - A.H. El-Astal; M.S. Hamada; M.M. Shabat (Functional Materials, 2008)
Some works have been carried out on studying metamaterials with negative electrical permittivity and negative magnetic permeability which called Left-handed materials (LHM), the propagation dispersion characteristics of magnetic waves in waveguide structures containing LHM. In this communication, we investigate the dispersion characteristics of magnetic surface waves in a metal-dielectric-ferrite (YIG)-LHM layered waveguide structure. Several characteristics of the propagation are also obtained especially on the non-reciprocal behavior. It has been noticed that the non-reciprocal behavior of the wave propagation has been obtained in the forward direction for the electromagnetic waves whereas this reciprocal behavior has been found in the forward and backward directions for the magneto-static surface waves. It should be stressed that the addition of the LHM layer to the above waveguide structure has been noticed to dominate the control of the direction of the dispersion curves from forward to backward wave propagation.